2013
DOI: 10.21630/mmns.2013.1.03
|View full text |Cite
|
Sign up to set email alerts
|

Suivi des observations de tortues marines sur la côte atlantique française depuis 1988

Abstract: Among the seven species of existing sea turtles, four can be seen in the Bay of Biscay and in the Manche. The leatherback turtle Dermochelys coriacea (Vandelli, 1761) and the loggerhead turtle Caretta caretta (Linnaeus, 1758) are the most seen species whereas the Kemp's ridley turtle Lepidochelys kempii (Garman, 1880) and the green turtle Chelonia mydas (Linnaeus, 1758) are seen more occasionally. The monitoring of the sightings done by the Aquarium La Rochelle and its Center of Studies and Cares for Sea Turt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…A rapid search of the literature confirms the presence of stranded or bycaught leatherbacks in all main hotspots identified in the active dispersal simulation: in the Azores area [50], off Mauritania [51, 52], along the Portuguese coast [47], in the Gulf of Cadiz [53] and along the Tunisian coast [54]. Stranded or bycaught leatherbacks are also reported in the Bay of Biscay [55], along the Galician coast [56], the Moroccan coast [57], and in the Mediterranean sea [58]. Interestingly, data indicate that leatherback stranding density is markedly higher along the Portuguese coast than in the bay of Biscay or Galicia [47].…”
Section: Resultsmentioning
confidence: 92%
“…A rapid search of the literature confirms the presence of stranded or bycaught leatherbacks in all main hotspots identified in the active dispersal simulation: in the Azores area [50], off Mauritania [51, 52], along the Portuguese coast [47], in the Gulf of Cadiz [53] and along the Tunisian coast [54]. Stranded or bycaught leatherbacks are also reported in the Bay of Biscay [55], along the Galician coast [56], the Moroccan coast [57], and in the Mediterranean sea [58]. Interestingly, data indicate that leatherback stranding density is markedly higher along the Portuguese coast than in the bay of Biscay or Galicia [47].…”
Section: Resultsmentioning
confidence: 92%
“…These sightings gather individuals stranded, bycaught in fishing nets or drifting at sea. Initiated in 1988 and compiling data from the four species found along Western Europe (leatherback, loggerhead, Kemp's ridley and green), this dataset has been partly published (Witt et al, 2007;Morinière and Dell'Amico, 2011). To be consistent with the tracking analysis, we restricted this dataset to the three species satellite tracked in our study, i.e., the loggerhead, the Kemp's ridley and the green turtle.…”
Section: Sightingsmentioning
confidence: 99%
“…Stranding events of sea turtles occur annually along the Western European coasts, including the Spanish (Bellido et al, 2010;Orós et al, 2016), Portuguese (Nicolau et al, 2016), British (Botterell et al, 2020) and French coasts (Witt et al, 2007;Morinière and Dell'Amico, 2011). Genetic analysis have demonstrated that immature loggerhead turtles stranded along the French Atlantic and English Channel coasts mostly originate from the North-East American coast (51%), and to a lesser extent to Cape Verde (26%) (Monzón-Argüello et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations